Growing up with tic disorders: an Italian survey on quality of life and access to care - V. Baglioni; D. Esposito; I. Notaristefano; G. Di Iorio; S. Romano; F. Pisani (Frontiers in Psychiatry)
BackgroundTourette Syndrome (TS) and chronic tic disorders (TD) are complex neuropsychiatric conditions often associated with comorbidities. Despite their prevalence, these disorders are frequently underdiagnosed and poorly managed due to limited healthcare access and lack of specialized services. An online survey was conducted in Italy to assess access to care and the impact of TS/TD on social, educational, and occupational life.MethodA nationwide online survey, including 100 participants (mean age 23.1, SD 14.6; M:F=77:33), was developed to assess diagnostic-therapeutic processes and quality of life (QoL) in TS/TD. The survey had three sections: 1) Access to Care, 2) Tic Severity, and 3) Impact of TS/TD.ResultsDiagnosis was delayed by an average of 7.7 years. The lack of clear information was a major issue, with caregivers reporting easier access to information than youths and adults with TS/TD (p= .042, OR: 0.37). Pharmacological treatment was the most common (53% currently, 63% previously), while psychotherapy was more common among children and early adolescents (50%) compared to older participants (25.6%) (p= .037). Specialized cognitive-behavioral treatments, such as EPT and HRT, were rare, with only 7% receiving HRT and none undergoing EPT. Comorbidities had a significantly greater impact on QoL than tics (p= .004, Cohen’s d=0.3).ConclusionThese findings highlight the need for improved access to specialized care, greater healthcare professional awareness, and enhanced support for individuals with TS/TD and their families, especially for early diagnosis and effective cognitive behavioral treatments.